Antibody response to seasonal influenza vaccination in patients with multiple sclerosis receiving immunomodulatory therapy. (6th January 2018) - Olberg, H. K.; Eide, G. E.; Cox, R. J.; Jul‐Larsen, Å.; Lartey, S. L.; Vedeler, C. A.; Myhr, K.‐M.
Abstract : Background and purpose: We have previously shown that patients with multiple sclerosis receiving immunomodulatory treatment have reduced seroprotection rates after influenza immunization. The aim of this study was to further investigate the influence of immunomodulatory therapies on the antibody response and seroprotection rates in patients immunized with seasonal influenza vaccine in 2012/2013 compared with healthy controls. Methods: Ninety patients receiving fingolimod, glatiramer acetate, interferon beta‐1a/1b, natalizumab or no therapy were compared with 62 healthy controls. All subjects received the inactivated split virus vaccine in 2012 and serum samples were collected pre‐vaccination and 3, 6 and 12 months post‐vaccination. The vaccine responses were evaluated by the hemagglutination inhibition assay and adjusted for age and gender. Results: No significant differences in rates of protection against H1N1 for interferon beta‐1a/1b and glatiramer acetate were observed as compared with controls at 3, 6 and 12 months. Fingolimod provided reduced protection at all time points post‐vaccination, whereas natalizumab displayed reduced protection at 3 and 6 months. Patients without immunomodulation did not display protection rates that were significantly different from the controls at 3 and 12 months. Conclusion: These findings suggest that patients with multiple sclerosis receiving fingolimod or natalizumab should be considered for a second dose of the vaccine in cases of insufficient protection. Our results further indicate that new immunomodulatory treatment regimens should be systematically evaluated for their influence on influenza‐specific vaccine responses.